2014
DOI: 10.1002/joc.3962
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the daily and extreme temperatures in the Qiantang River basin, China

Abstract: Temporal and spatial changes in the annual and seasonal temperatures in a typical basin of the Qiantang River were analysed based on the time series databases of daily temperatures from 14 meteorological stations. Both the Mann-Kendall (MK) trend test and simple linear regression analyses were employed to detect trends in the mean and extreme temperatures. The temperature changes during the three periods of 1960-1990, 1960-2000 and 1960-2006 were investigated at each meteorological station and over the entire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Extreme precipitation has a profound impact on society, property, and human welfare around the world (Easterling et al, 2000;Greenough et al, 2001;Véronique et al, 2014;Xia et al, 2015) and can result in deadly and destructive natural disasters (Plummer et al, 1999;Jonkman, 2005;Potop et al, 2014). The North China Plain (NCP; 32°-40.5°N, 115°-121°E) is a politically and economically key region with a dense population and substantial grain production.…”
Section: Introductionmentioning
confidence: 99%
“…Extreme precipitation has a profound impact on society, property, and human welfare around the world (Easterling et al, 2000;Greenough et al, 2001;Véronique et al, 2014;Xia et al, 2015) and can result in deadly and destructive natural disasters (Plummer et al, 1999;Jonkman, 2005;Potop et al, 2014). The North China Plain (NCP; 32°-40.5°N, 115°-121°E) is a politically and economically key region with a dense population and substantial grain production.…”
Section: Introductionmentioning
confidence: 99%
“…Extreme weather events, such as frequent droughts and floods, have profound impacts on both economic and human welfare (Xia et al 2015). Extreme precipitation events are among the most deadly and destructive natural disasters worldwide (Plummer et al 1999;Potop et al 2014) and the corresponding losses of life and property have demonstrated the importance of relevant research (Easterling et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…This filtering was made in order to minimize the interference of noise on the cluster analysis Berndtsson 1996, Uvo 2003). The method of Ward was applied to establish the numbers of HG (Munõz-Dias and Rodrigo 2004, Lyra et al 2014, Rodriguez et al 2016, and the clustering validation was based on the physical understanding of the geographical expression of the cluster in the study area. From the identified homogeneous groups, the MJJ time series of precipitation at each HG was calculated from the rainfall stations belonging to each HG.…”
Section: Spatial-temporal Patterns Of Mjj Precipitation and Homogeneomentioning
confidence: 99%